Dispersion, liquid composition, and method for producing same

JP7635720B2Active Publication Date: 2025-02-26AGC INC
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021565613
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-06
Filing Date
2020-12-16
Publication Date
2025-02-26
Estimated Expiration
2040-12-16

AI Technical Summary

Benefits of technology

【0006】 本発明によれば、ポリテトラフルオロエチレンの粒子と所定のテトラフルオロエチレン系ポリマーの粒子を含む、液物性(分散性、粘度等)に優れた水系分散液が得られる。また、かかる水系分散液の容易な製造に適した、所定のテトラフルオロエチレン系ポリマーの粒子と、所定の水溶性化合物とを含む液状組成物が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635720000001
    Figure 0007635720000001
Patent Text Reader

Abstract

[Problem] To provide a dispersion liquid that contains different types of tetrafluoroethylene-based polymer particles and that enable formation of a molded article having excellent liquid properties and excellent various physical properties (in particular, adhesiveness with respect to substrates). [Solution] The dispersion liquid according to the present invention contains: polytetrafluoroethylene particles; particles of a tetrafluoroethylene-based polymer including a unit based on perfluoro(alkyl vinyl ether); at least one water-soluble compound having a boiling point of 100°C or more and selected from the group consisting glycols, monoethers of glycols, and monoacetates of glycols; and water.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dispersion liquid of a specific embodiment containing polytetrafluoroethylene particles, a method for producing the same, a liquid composition that can be suitably used for producing the dispersion liquid, and methods for producing the same. [Background technology]

[0002] Dispersions containing particles of tetrafluoroethylene polymers are known as coating agents for forming layers having excellent chemical resistance, water and oil repellency, heat resistance and electrical properties on the surfaces of substrates. Patent Document 1 describes an aqueous dispersion containing polytetrafluoroethylene particles, particles of a tetrafluoroethylene-based polymer containing units based on perfluoro(alkyl vinyl ether), a high molecular weight water-soluble polymer, and water, and a thin film formed by baking a coating formed from the aqueous dispersion. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2008 / 018400 Summary of the Invention [Problem to be solved by the invention]

[0004] The present inventors have found that, although the occurrence of cracks during the formation of a coating is suppressed by the water-soluble polymer in such an aqueous dispersion, the liquid properties (dispersibility, viscosity, etc.) are likely to deteriorate. Furthermore, the present inventors have found that, conversely, the properties and physical properties of the thin film formed are likely to deteriorate due to decomposition of the water-soluble polymer (generation of decomposition gas) or residues of the water-soluble polymer upon baking of the coating. The present invention aims to provide a dispersion containing particles of different tetrafluoroethylene-based polymers, which has excellent liquid properties and can form molded articles having excellent physical properties (particularly, excellent adhesion to substrates). Another object of the present invention is to provide a liquid composition that can be suitably used for producing such a dispersion. A further object of the present invention is to provide such a dispersion and a method for producing such a dispersion. [Means for solving the problem]

[0005] The present invention has the following aspects. [1] A dispersion comprising: particles of polytetrafluoroethylene; particles of a tetrafluoroethylene-based polymer containing units based on perfluoro(alkyl vinyl ether); at least one water-soluble compound having a boiling point of 100°C or higher selected from the group consisting of glycols, glycol monoethers, and glycol monoacetates; and water. [2] The dispersion liquid according to [1], wherein the water-soluble compound is a glycol monoalkyl ether, a glycol monoaryl ether, a glycol monoalkyl ether acetate, or a glycol monoaryl ether acetate. [3] The dispersion liquid according to [1] or [2], wherein the tetrafluoroethylene-based polymer is a tetrafluoroethylene-based polymer having an oxygen-containing polar group containing a unit based on perfluoro(alkyl vinyl ether), or a tetrafluoroethylene-based polymer having no oxygen-containing polar group and containing the unit in an amount of 2.0 to 5.0 mol % based on all units. [4] The dispersion liquid according to any one of the above [1] to [3], wherein the polytetrafluoroethylene particles have an average particle size of 0.01 to 1 μm, and the tetrafluoroethylene-based polymer particles have an average particle size of 0.01 to 10 μm. [5] The dispersion according to any one of the above [1] to [4], wherein the ratio by mass of the content of the tetrafluoroethylene-based polymer to the content of the polytetrafluoroethylene is 0.4 or less. [6] The dispersion liquid according to any one of [1] to [5] above, wherein the ratio by mass of the content of the water-soluble compound to the content of the water is 2 or less. [7] A method for producing a laminate, comprising applying the dispersion liquid according to any one of [1] to [6] above to a surface of a substrate, heating the substrate to form a polymer layer containing the polytetrafluoroethylene and the tetrafluoroethylene-based polymer, and obtaining a laminate having a substrate layer constituted by the substrate and the polymer layer. [8] A method for producing an impregnated woven fabric, comprising impregnating a woven fabric with the dispersion liquid of any one of [1] to [6] above and heating the resulting fabric to obtain an impregnated woven fabric containing the polytetrafluoroethylene and the tetrafluoroethylene-based polymer. [9] A method for producing the dispersion according to any one of the above [1] to [6], comprising mixing an aqueous dispersion containing the polytetrafluoroethylene particles with a liquid composition containing the tetrafluoroethylene-based polymer particles and the water-soluble compound to obtain the dispersion.

[10] A liquid composition comprising particles of a tetrafluoroethylene-based polymer containing units based on perfluoro(alkyl vinyl ether) and at least one water-soluble compound having a boiling point of 100°C or higher selected from the group consisting of glycols, glycol monoethers, and glycol monoacetates.

[11] The liquid composition according to

[10] , further comprising water.

[12] The liquid composition according to either

[10] or

[11] above, comprising 5 to 50 mass % of the tetrafluoroethylene-based polymer.

[13] The liquid composition according to any one of

[10] to

[12] above, wherein the water-soluble compound has an HLB value of 1 to 18.

[14] The liquid composition according to any one of the above

[10] to

[13] , having a viscosity of 1000 mPa·s or less.

[15] A method for producing a liquid composition, comprising subjecting a liquid composition containing particles of a tetrafluoroethylene-based polymer containing units based on perfluoro(alkyl vinyl ether) and at least one water-soluble compound having a boiling point of 100°C or higher selected from the group consisting of glycols, glycol monoethers, and glycol monoacetates to a wet milling method to obtain a liquid composition containing the tetrafluoroethylene-based polymer particles and the water-soluble compound. Effect of the Invention

[0006] According to the present invention, an aqueous dispersion containing polytetrafluoroethylene particles and a specific tetrafluoroethylene-based polymer particles and having excellent liquid properties (dispersibility, viscosity, etc.) can be obtained. In addition, a liquid composition containing the specific tetrafluoroethylene-based polymer particles and a specific water-soluble compound, which is suitable for easy production of such an aqueous dispersion, can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The following terms have the following meanings: The "melting temperature (melting point) of a polymer" is the temperature corresponding to the maximum value of the melting peak measured by differential scanning calorimetry (DSC). The "viscosity of the dispersion" is the viscosity of the dispersion measured using a Brookfield viscometer at 25° C. and a rotation speed of 30 rpm. The "thixotropy ratio of the dispersion" is a value calculated by dividing the viscosity of the dispersion measured at a rotation speed of 30 rpm by the viscosity of the dispersion measured at a rotation speed of 60 rpm. The "static surface tension" is determined by the Wilhelmy method using an automatic surface tensiometer CBVP-Z type (manufactured by Kyowa Interface Science Co., Ltd.) and a 0.1% by mass aqueous solution of the water-soluble compound. "Dynamic surface tension" refers to the dynamic surface tension of a 0.1% by mass aqueous solution of a water-soluble compound at 25°C with a bubble generation period of 6 Hz according to the maximum bubble pressure method, and is the value measured by the maximum bubble pressure method in an environment at 25°C by immersing the sensor of a dynamic surface tensiometer Theta t60 manufactured by Eiko Seiki Co., Ltd. in the aqueous solution containing 0.1% by mass of the water-soluble compound. The measurement is performed with the bubble generation period of the aqueous solution set to 6 Hz. "Average particle size (D50)" is the volume-based cumulative 50% diameter of particles determined by laser diffraction / scattering. In other words, the particle size distribution of particles is measured by laser diffraction / scattering, the total volume of the particle group is set to 100%, and a cumulative curve is calculated. The particle size is the point on the cumulative curve where the cumulative volume is 50%. The "90% cumulative volume diameter of particles (D90)" is the volume-based cumulative 90% diameter of particles determined in a similar manner. The "unit" in a polymer may be an atomic group formed directly from a monomer by a polymerization reaction, or may be an atomic group in which a part of the structure is converted by treating a polymer obtained by a polymerization reaction with a predetermined method. A unit based on monomer A contained in a polymer is also simply referred to as a "monomer A unit".

[0008] The dispersion of the present invention (present dispersion) contains particles of polytetrafluoroethylene (PTFE), particles of a tetrafluoroethylene-based polymer (hereinafter also referred to as "PFA") containing units based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE units), at least one water-soluble compound having a boiling point of 100°C or higher selected from the group consisting of glycol, glycol monoether, and glycol monoacetate, and water. PFA is a polymer containing units based on tetrafluoroethylene (TFE) (TFE units) and is a different polymer from PTFE. This dispersion has high dispersion stability and excellent liquid properties (viscosity or thixotropy ratio), and the molded products formed from it have excellent properties (especially adhesion to substrates). The reasons for this are not entirely clear, but are thought to be as follows.

[0009] The water-soluble compound contained in the present dispersion is a compound with a specific boiling point and a structure derived from glycol (structure represented by the formula: HO-Q-OH; in the formula, Q is a divalent aliphatic hydrocarbon group, and two hydroxyl groups are bonded to different carbon atoms). It is believed that such a compound is highly soluble in the present dispersion containing polymer particles and exerts various functions. Specific functions include acting as a dispersant that effectively covers the surface of the polymer particles and improves their dispersibility, acting as a dispersion medium that itself makes the polymer particles dispersoids, and acting as a viscosity adjuster or thixotropy imparting agent that stabilizes the state of the dispersion (viscosity, thixotropy ratio, etc.).

[0010] PTFE has unique physical properties, such as fibril nature, and therefore, although PTFE particles have a certain degree of water dispersibility, they are easily altered by physical stress (shear, etc.), chemical changes (temperature, pH, etc.), or changes over time. PFA is a crystalline polymer containing TFE units, and its particles also have water-dispersibility and are less susceptible to the above-mentioned stresses and changes in an aqueous dispersion. In this dispersion, the action of the water-soluble compound enhances the interaction between the PTFE particles and the PFA particles, resulting in the formation of loose pseudo-secondary particles in at least a portion of the particles of both polymers, which is thought to improve the dispersion stability of the entire dispersion. Furthermore, since the boiling point of the water-soluble compound is within a predetermined range, and the water-soluble compound is also removed by evaporation when the water is removed from the dispersion by heating, a molded article having various excellent physical properties can be formed. Specifically, the dispersion can be used to form a molded article having the high physical properties of PTFE and the adhesiveness derived from the physical properties of PFA.

[0011] The PTFE in the present invention may be a homopolymer of TFE, or a copolymer of TFE and a very small amount of comonomer (PAVE, hexafluoropropylene, fluoroalkylethylene, etc.). The latter PTFE preferably contains 99.9 mol% or more of TFE units based on the total units. The PTFE may also be a low molecular weight PTFE. The melt viscosity of PTFE at 380℃ is 1×10 2 Pa s or more is preferable, and 1×10 3 More preferably, 1×10 9 The upper limit of the melt viscosity is usually 1×10 10 Pa·s. The PTFE preferably has fibrillary properties.

[0012] The PTFE particles in the present invention are preferably made of PTFE. The PTFE content in the PTFE particles is preferably 80% by mass or more, and more preferably 100% by mass. Other components that may be included in the particles of PTFE include aromatic polyesters, polyamideimides, thermoplastic polyimides, polyphenylene ethers, and polyphenylene oxides. The D50 of the PTFE particles is preferably 1 μm or less, more preferably 0.5 μm or less, and even more preferably 0.4 μm or less. The D50 of the PTFE particles is preferably 0.01 μm or more, and more preferably 0.1 μm or more. The D90 of the PTFE particles is preferably 1 μm or less, and more preferably 0.5 μm or less.

[0013] The PFA in the present invention is a polymer containing TFE units and PAVE units. The melting temperature of PFA is preferably from 260 to 325°C, and more preferably from 290 to 320°C. It is preferable that PFA contains 2 to 10 mol % or more of PAVE units based on the total units. In this case, due to the above-mentioned mechanism of action, the interaction between the PTFE particles and the PFA particles is further enhanced, and the dispersion stability of the present dispersion is easily improved. Examples of PAVE include CF2=CFOCF3 (PMVE), CF2=CFOCF2CF3, CF2=CFOCF2CF2CF3 (PPVE), and CF2=CFOCF2CF2CF2CF3, with PMVE and PPVE being preferred.

[0014] The PFA preferably has an oxygen-containing polar group (polar functional group). Since the PFA having the oxygen-containing polar group has a high affinity with water-soluble compounds, the PFA is more likely to have a stronger interaction with the PTFE particles due to the above-mentioned mechanism of action, and is more likely to improve the dispersion stability of the present dispersion. The oxygen-containing polar group may be contained in a unit in the PFA, or may be contained in an end group of the main chain of the polymer. The former embodiment includes PFAs containing units based on monomers having oxygen-containing polar groups. Examples of the latter embodiment include PFA having an oxygen-containing polar group as an end group derived from a polymerization initiator, a chain transfer agent, etc., and PFA having an oxygen-containing polar group obtained by plasma treatment or ionizing radiation treatment.

[0015] The oxygen-containing polar group is preferably a hydroxyl group-containing group or a carbonyl group-containing group, and from the viewpoint of further enhancing the dispersion stability of the present dispersion, a carbonyl group-containing group is more preferred. The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, more preferably -CF2CH2OH or -C(CF3)2OH. The carbonyl group-containing group is a group containing a carbonyl group (>C(O)), and is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.), or a carbonate group (-OC(O)O-).

[0016] When PFA has a carbonyl group-containing group, the number of carbonyl group-containing groups in the PFA is 1×10 6 The number of carbonyl-containing groups per unit is preferably 10 to 5000, and more preferably 50 to 2000. The number of carbonyl-containing groups in PFA can be quantified by the composition of the polymer or the method described in WO 2020 / 145133. The monomer having an oxygen-containing polar group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (also called himic anhydride; hereinafter, also referred to as "NAH").

[0017] Specific preferred examples of PFA include PFAs having a melting temperature of 260 to 320°C, which contain TFE units and PAVE units, with the PAVE units accounting for 1.0 to 5.0 mol% of the total units; more preferred are PFAs (1) having an oxygen-containing polar group, which contain TFE units, PAVE units, and units based on a monomer having an oxygen-containing polar group, and PFAs (2) which do not have an oxygen-containing polar group, which contain TFE units and PAVE units, and which contain 2.0 to 5.0 mol% of PAVE units based on the total units. These PFA particles not only have excellent dispersion stability, but also tend to be distributed more densely and homogeneously in the molded article (polymer layer, etc.) formed from this dispersion. Furthermore, they tend to form microspherulites in the molded article, which tends to increase adhesion with other components. As a result, molded articles that have high physical properties of each of the three components are more likely to be obtained.

[0018] PFA (1) preferably contains, based on all units, 90 to 99 mol % of TFE units, 1.5 to 5.0 mol % of PAVE units, and 0.01 to 3 mol % of units based on a monomer having an oxygen-containing polar group. Specific examples of PFA (1) include the polymers described in WO 2018 / 16644. PFA (2) is composed only of TFE units and PAVE units, and preferably contains 95.0 to 98.0 mol % of TFE units and 2.0 to 5.0 mol % of PAVE units based on all units. The content of the PAVE unit in PFA (2) is preferably 2.1 mol % or more, and more preferably 2.2 mol % or more, based on all units.

[0019] In addition, the polymer (2) having no oxygen-containing polar group is defined as having a number of carbon atoms constituting the polymer main chain that is less than 1×10 6 This means that the number of oxygen-containing polar groups in the polymer per unit is less than 500. The number of the oxygen-containing polar groups is preferably 100 or less, more preferably less than 50. The lower limit of the number of the oxygen-containing polar groups is usually 0. PFA (2) may be produced using a polymerization initiator or a chain transfer agent that does not generate an oxygen-containing polar group as a terminal group of the polymer chain, or may be produced by fluorinating an F polymer having an oxygen-containing polar group (such as an F polymer having an oxygen-containing polar group derived from a polymerization initiator at the terminal group of the polymer main chain). Examples of the fluorination method include a method using fluorine gas (see JP 2019-194314 A, etc.).

[0020] The PFA particles in the present invention are preferably made of PFA. The PFA content in the PFA particles is preferably 80% by mass or more, and more preferably 100% by mass. Other components that may be included in the PFA particles include resins or inorganic substances different from PFA, such as aromatic polyesters, polyamideimides, thermoplastic polyimides, polyphenylene ethers, and polyphenylene oxides. Examples of inorganic substances include silicon oxide (silica), metal oxides (beryllium oxide, cerium oxide, alumina, soda alumina, magnesium oxide, zinc oxide, titanium oxide, etc.), boron nitride, and magnesium metasilicate (steatite).

[0021] PFA particles containing a resin or inorganic material different from PFA preferably have a core-shell structure with PFA as the core and the above-mentioned resin or inorganic material as the shell, or a core-shell structure with PFA as the shell and the above-mentioned resin or inorganic material as the core. Such PFA particles are obtained, for example, by bonding (collision, aggregation, etc.) PFA particles and the above-mentioned resin or inorganic material particles. The D50 of the PFA particles is preferably 5 μm or less, more preferably 0.4 μm or less. The D50 of the PFA particles is preferably 0.01 μm or more, more preferably 0.1 μm or more. The D90 of the PFA particles is preferably 10 μm or less, more preferably 5 μm or less.

[0022] The PTFE content in the present dispersion is preferably 10% by mass or more, more preferably 20% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less. The PFA content in the present dispersion is preferably 1% by mass or more, more preferably 2% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less. The ratio by mass of the PFA content to the PTFE content in the present dispersion (mass ratio) is preferably 0.4 or less, more preferably 0.2 or less, and even more preferably 0.1 or less. The ratio is preferably 0.01 or more, and more preferably 0.05 or more. Within this range, not only is the dispersion stability of the present dispersion more likely to be improved due to the above-mentioned mechanism of action, but the physical properties of PTFE are highly expressed in the formed molded article, and the adhesion to the substrate is also likely to be improved.

[0023] The water-soluble compound in the present dispersion is at least one compound selected from the group consisting of glycols, glycol monoethers, and glycol monoacetates, and is a compound having a boiling point of 100° C. or higher. The water-soluble compound may be one type or two or more types. In the case of two or more types, different water-soluble compounds are preferably compatible with each other. The water-soluble compound is preferably a non-polymeric nonionic compound. The molecular weight of the water-soluble compound is preferably 60 to 2,000, and more preferably 100 to 1,000. The boiling point of the water-soluble compound is 100° C. or higher, preferably 100 to 400° C., more preferably 100 to 300° C., further preferably 105 to 275° C., and particularly preferably 200 to 250° C. In this case, when water is heated and removed from the dispersion to form a molded article, the water-soluble compound is less likely to remain in the molded article, and various physical properties (electrical insulation, etc.) of the molded article are likely to be improved. In addition, since the water-soluble compound is removed more slowly than water, the smoothness of the surface of the molded article is likely to be further improved.

[0024] The water-soluble compound in the present dispersion can also be said to be a compound having a structure derived from an oxyalkylene group. The molecular weight dispersity of the water-soluble compound is preferably less than 2.0, more preferably not more than 1.8, and the lower limit of the molecular weight dispersity is preferably more than 1.0. The HLB value of the water-soluble compound is preferably 1 to 18, more preferably 10 to 16, and further preferably 10 to 14. The HLB value is a value calculated by the Griffin equation, and is determined by dividing the molecular weight of the polyoxyalkylene portion in the water-soluble compound by the molecular weight of the water-soluble compound and multiplying the result by 20. The static surface tension of the water-soluble compound is preferably 28 N / cm or less, more preferably 20 N / cm or more, and even more preferably 22 N / cm or more. The dynamic surface tension of the water-soluble compound is preferably 40 mN / m or less, more preferably 35 mN / m or less, and the dynamic surface tension is preferably 20 mN / m or more. When the physical properties of the water-soluble compound satisfy these ranges, the above-mentioned mechanism of action is enhanced, and the physical properties of the present dispersion, in particular a dispersion or liquid composition with low viscosity, are easily obtained.

[0025] Specific examples of glycols include 2,4-diethyl-1,5-pentanediol [264°C], 1,2-propanediol [187°C], 2-methyl-2,4-pentanediol [197°C], 2-butyl-2-ethyl-1,3-propanediol [178°C], ethylene glycol [198°C], 2-ethyl-1,3-hexanediol [241-249°C], diethylene glycol [245°C], and triethylene glycol [288°C].

[0026] Specific examples of glycol monoethers include glycol monoalkyl ethers such as diethylene glycol monomethyl ether [194°C], diethylene glycol monoethyl ether [202°C], diethylene glycol monobutyl ether [230°C], ethylene glycol mono-2-ethylhexyl ether [229°C], dipropylene glycol monobutyl ether [222-232°C], triethylene glycol monomethyl ether [248°C] and tripropylene glycol monobutyl ether [242°C], and glycol monoaryl ethers such as propylene glycol monophenyl ether [243°C].

[0027] Specific examples of glycol monoacetates include diethylene glycol monoethyl ether acetate [217°C] and diethylene glycol monobutyl ether acetate [247°C]. The temperatures in parentheses in the above examples are the boiling points of the respective compounds.

[0028] The water-soluble compound is preferably a glycol monoalkyl ether, a glycol monoaryl ether, a glycol monoalkyl ether acetate, or a glycol monoaryl ether acetate, and more preferably a glycol monoalkyl ether. The glycol monoalkyl ether is preferably a polyoxyethylene glycol monoalkyl ether. The number of oxyethylene units (-OCH2CH2-) contained in the polyoxyethylene ethylene glycol is preferably 1 to 10, and the monoalkyl ether group is preferably highly branched.

[0029] Specific preferred examples of the water-soluble compound include polyoxyethylene decyl ether, polyoxyethylene undecyl ether, polyoxyethylene dodecyl ether, polyoxyethylene tridecyl ether, polyoxyethylene tetradecyl ether, triethylene glycol monomethyl ether, polyethylene glycol trimethylnonyl ether, ethylene glycol mono-2-ethylhexyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, dipropylene glycol monobutyl ether, triethylene glycol monomethyl ether, tripropylene glycol monobutyl ether, propylene glycol monophenyl ether, diethylene glycol monoethyl ether acetate, and diethylene glycol monobutyl ether acetate.

[0030] The water-soluble compounds are available as commercial products (e.g., "Tergitol" manufactured by Dow Chemical Company), specifically, "Tergitol TMN-100X" (manufactured by Dow Chemical Company), "Lutensol TO8", "Lutensol XL70", "Lutensol XL80", "Lutensol XL90", "Lutensol XP80", "Lutensol M5" (all manufactured by BASF), "Newcol 1305", "Newcol 1308FA", "Newcol 1310" (all manufactured by Nippon Nyukazai Co., Ltd.), "Leocol TDN-90-80", "Leocol SC-90" (all manufactured by Lion Specialty Chemicals).

[0031] The water content in the present dispersion is preferably 10% by mass or more, more preferably 20% by mass or more, and is preferably 70% by mass or less, more preferably 60% by mass or less. The content of the water-soluble compound in the present dispersion is preferably 1% by mass or more, more preferably 5% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less. The ratio by mass of the content of the water-soluble compound to the content of water in the present dispersion (mass ratio) is preferably not more than 2, more preferably not more than 1.5. The ratio is preferably not less than 0.1, more preferably not less than 0.5. Within this range, the dispersion stability of the present dispersion is more likely to be improved due to the interaction between the PTFE particles and the PFA particles, due to the above-mentioned mechanism of action.

[0032] In addition to the PTFE particles, PFA particles, water, and water-soluble compounds, the present dispersion may contain other components such as a surfactant, a thixotropy imparting agent, a viscosity modifier, an antifoaming agent, a silane coupling agent, a dehydrating agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive agent, a release agent, a surface treatment agent, a flame retardant, and various fillers. From the viewpoints of further improving the dispersion stability and improving the particle settling property and handling property, the present dispersion preferably further contains a surfactant. The surfactant is preferably nonionic.

[0033] The hydrophilic site of the surfactant preferably has an oxyalkylene group or an alcoholic hydroxyl group. The oxyalkylene group may be composed of one type or two or more types. In the latter case, the different types of oxyalkylene groups may be arranged randomly or in a block form. The oxyalkylene group is preferably an oxyethylene group.

[0034] The hydrophobic portion of the surfactant preferably has an acetylene group, a polysiloxane group, a perfluoroalkyl group, or a perfluoroalkenyl group, i.e., the surfactant is preferably an acetylene-based surfactant, a silicone-based surfactant, or a fluorine-based surfactant. Among these, the surfactant is more preferably a fluorosurfactant, and even more preferably a fluorosurfactant having a hydroxyl group (particularly an alcoholic hydroxyl group) or an oxyalkylene group and a perfluoroalkyl group or a perfluoroalkenyl group.

[0035] Specific examples of such surfactants include the "Ftergent" series (manufactured by Neos), the "Surflon" series (manufactured by AGC Seimi Chemical), the "Megafac" series (manufactured by DIC), and the "Unidyne" series (manufactured by Daikin Industries, Ltd.). When the present dispersion contains a surfactant, the content thereof is preferably 1 to 15% by mass, which makes it easier to improve the dispersion stability of the present dispersion.

[0036] The dispersion may contain other resins (polymers) in addition to PTFE and PFA. The other resins may be thermosetting resins or thermoplastic resins. Examples of other resins include epoxy resins, maleimide resins, urethane resins, elastomers, polyimides, polyamic acids, polyamideimides, polyphenylene ethers, polyphenylene oxides, and liquid crystal polyesters.

[0037] A preferred embodiment of the other resin is an aromatic polymer. The aromatic polymer is preferably an aromatic polyimide or an aromatic polyamic acid, and more preferably a thermoplastic aromatic polyimide. In this case, when forming a molded product from the dispersion, the powder fall of the PTFE particles and the PFA particles is suppressed, and the adhesiveness is easily improved. When the present dispersion contains an aromatic polymer, its content is more preferably 5 to 25% by mass. The ratio by mass of the content of the aromatic polymer to the total content of PTFE and PFA (mass ratio) is preferably 1.0 or less, more preferably 0.1 to 0.7. When the present dispersion contains another resin, it may be produced by mixing the present dispersion with particles of the other resin, or it may be produced by mixing the present dispersion with a varnish containing the other resin.

[0038] The viscosity of the dispersion is preferably 50 mPa·s or more, more preferably 100 mPa·s or more. The viscosity of the dispersion is preferably 1000 mPa·s or less, more preferably 800 mPa·s or less, even more preferably 500 mPa·s or less, and particularly preferably 360 mPa·s or less. The thixotropy ratio of the present dispersion is preferably 1.0 or more, more preferably 3.0 or less, and even more preferably 2.0 or less. Due to the above-mentioned mechanism of action, the present dispersion can be easily adjusted to have a viscosity or thixotropy within the above range, and is likely to have excellent dispersion stability and handleability. The pH of the present dispersion is preferably from 1 to 8. In such a case, the present dispersion tends to have excellent hue and storage stability.

[0039] The method for producing the dispersion includes a method of mixing an aqueous dispersion containing PTFE particles with a liquid composition containing PFA particles and a water-soluble compound, and a method of mixing an aqueous dispersion containing PTFE particles with an aqueous dispersion containing PFA particles and a water-soluble compound. In the latter method, the water-soluble compound may be mixed after mixing both aqueous dispersions, or may be mixed in advance with either one of the aqueous dispersions. It is preferable to mix the aqueous dispersion and the liquid composition in a well-dispersed state. For example, when solids are precipitated in the liquid composition, it is preferable to disperse the liquid composition with a homodisper immediately before mixing, and then disperse the liquid composition with a homogenizer. In particular, when using a liquid composition stored at 0 to 40°C, it is preferable to carry out these dispersion treatments. The aqueous dispersion containing PTFE particles may be prepared by dispersing PTFE particles in water, or a commercially available aqueous dispersion may be used as is.

[0040] A liquid composition containing PFA particles and a water-soluble compound (hereinafter also referred to as "the liquid composition") is preferably prepared by dispersing PFA particles in a water-soluble compound. The liquid composition is preferably a dispersion in which PFA particles are dispersed in a water-soluble compound. The dispersion medium in the liquid composition preferably contains a water-soluble compound as a main component, and preferably consists of a water-soluble compound. Incidentally, the term "contains a water-soluble compound as a main component" means that the content of the water-soluble compound in the dispersion medium is 90% by mass or more. Examples of the dispersion medium other than the water-soluble compound include water, amide, and ester, and water is preferred.

[0041] The content of PFA in the present liquid composition is preferably from 5 to 50% by mass, more preferably from 10 to 40% by mass. The content of the water-soluble compound in the present liquid composition is preferably 60 to 95 mass %, more preferably 70 to 90 mass %. When the present liquid composition contains a dispersion medium other than the water-soluble compound, the content thereof is preferably 1 to 10 mass %. The aspects of the PFA, PFA particles, or water-soluble compound in the present liquid composition, including preferred aspects, are the same as those in the present dispersion. The present liquid composition may contain other components in addition to the PFA particles and the water-soluble compound. The aspects of these other components, including the preferred aspects, are the same as those in the present dispersion. Specifically, the present liquid composition preferably further contains a surfactant, the embodiment of which is the same as that of the present dispersion. When the liquid composition contains a surfactant, the content of the surfactant is preferably from 1 to 30% by mass.

[0042] The liquid composition may further be subjected to a wet milling method, which makes it easier to adjust the dispersion state and particle size of the PFA particles in the liquid composition. The D50 of the adjusted PFA particles is preferably 1 μm or less, more preferably 0.8 μm or less. The D50 of the PFA particles is preferably 0.1 μm or more, more preferably 0.2 μm or more. By using the liquid composition containing such PFA fine particles, it is possible to produce a higher density (dense) dispersion. An example of the wet mill method is a wet jet mill method. In the wet jet mill method, the liquid composition is subjected to the jet mill preferably 20 to 60 times, more preferably 30 to 50 times, in which case a sufficient atomization effect can be obtained without impairing the state of the PFA particles.

[0043] This dispersion also has excellent dispersion stability and storage stability, and can form molded articles that have excellent crack resistance and strong adhesion to substrates without impairing the physical properties of PTFE. This dispersion is applied to the surface of a substrate and heated to form a polymer layer containing PTFE and PFA (hereinafter also referred to as "F layer"), thereby producing a laminate (this laminate) having a substrate layer composed of the above substrate and an F layer.

[0044] In the production of the present laminate, it is sufficient that an F layer is formed on at least one surface of the substrate, and an F layer may be formed on only one surface of the substrate, or an F layer may be formed on both surfaces of the substrate. The surface of the substrate may be surface-treated with a silane coupling agent or the like. The dispersion can be applied using any of the following coating methods: spraying, roll coating, spin coating, gravure coating, microgravure coating, gravure offset, knife coating, kiss coating, bar coating, die coating, fountain-meyer bar, and slot die coating.

[0045] The F layer is preferably formed by removing the dispersion medium by heating and then calcining the polymer by heating, and is particularly preferably formed by heating the substrate to a temperature (100 to 300°C) at which the dispersion medium volatilizes, and further heating the substrate to a temperature range (300 to 400°C) at which the polymer is calcined. In other words, the F layer preferably contains a calcined product of PTFE and PFA. The thickness of the F layer is preferably 0.1 μm or more, more preferably 1 μm or more. The upper limit of the thickness is 100 μm. Within this range, an F layer with excellent crack resistance can be easily formed. The peel strength between the F layer and the base layer is preferably 10 N / cm or more, more preferably 15 N / cm or more. The above peel strength is preferably 100 N / cm or less. By using the present dispersion, the present laminate can be easily formed without impairing the physical properties of the PTFE in the F layer.

[0046] Examples of the material for the substrate include copper, aluminum, iron, glass, resin, silicon, and ceramics. The shape of the substrate may be flat, curved or uneven, and may further be any of foil, plate, film and fiber. Specific examples of the present laminate include a metal-clad laminate having a metal foil and an F layer on at least one surface of the metal foil, and a multilayer film having a polyimide film and an F layer on both surfaces of the polyimide film. These present laminates have excellent physical properties such as electrical properties, and are suitable as printed circuit board materials, etc. Specifically, such present laminates can be used to manufacture flexible printed circuit boards and rigid printed circuit boards.

[0047] The dispersion is impregnated into a woven fabric and then dried by heating to obtain an impregnated woven fabric (the present woven fabric) in which the woven fabric is impregnated with PTFE and PFA. The present woven fabric can also be said to be a coated woven fabric in which the woven fabric is coated with an F layer. The woven fabric is preferably a glass fiber woven fabric, a carbon fiber woven fabric, an aramid fiber woven fabric, or a metal fiber woven fabric, and more preferably a glass fiber woven fabric or a carbon fiber woven fabric. The woven fabric may be treated with a silane coupling agent from the viewpoint of increasing the adhesion to the F layer. The total content of PTFE and PFA in the present woven fabric is preferably 30 to 80% by mass. Methods for impregnating a woven fabric with the present dispersion include a method of immersing a woven fabric in the present dispersion and a method of coating a woven fabric with the present dispersion.

[0048] When drying the woven fabric, the polymer may be calcined. A method for calcining the polymer includes passing the woven fabric through a ventilated drying oven in an atmosphere of 300 to 400° C. The drying of the woven fabric and the calcination of the polymer may be carried out in one step. This woven fabric has excellent properties such as high adhesion (bonding) between the F layer and the woven fabric, high surface smoothness, little distortion, etc. By thermocompression bonding this woven fabric and metal foil, a metal clad laminate with high peel strength and resistance to warping is obtained, which can be suitably used as a printed circuit board material.

[0049] In the manufacture of the present woven fabric, the woven fabric impregnated with the present dispersion may be applied to the surface of a substrate, and then heated and dried to form an impregnated woven fabric layer containing PTFE, PFA, and the woven fabric, thereby manufacturing a laminate in which the substrate and the impregnated woven fabric layer are laminated in this order. The mode is not particularly limited, and the woven fabric impregnated with the present dispersion may be applied to a part or all of the inner wall surface of a member such as a tank, pipe, or container, and the member may be heated while rotating to form an impregnated woven fabric layer on a part or all of the inner wall surface of the member. This manufacturing method is also useful as a method for lining the inner wall surface of a member such as a tank, pipe, or container.

[0050] As explained above, the present dispersion has excellent dispersion stability and can be highly impregnated into porous or fibrous materials. Such porous or fibrous materials include materials other than the above-mentioned woven fabrics, specifically, plate-like, columnar, or fibrous materials. These materials may be pretreated with a curable resin, a silane coupling agent, or the like, and may further be filled with an inorganic filler. These materials may also be twisted together to form threads, cables, or wires. When twisting together, an intermediate layer made of another polymer such as polyethylene may be disposed. An embodiment in which such a material is impregnated with the present dispersion to produce a molded product includes an embodiment in which a fibrous material carrying a curable resin or a cured product thereof is impregnated with the present dispersion.

[0051] Examples of fibrous materials include high strength, low elongation fibers such as carbon fibers, aramid fibers, and silicon carbide fibers. As the curable resin, a thermosetting resin such as an epoxy resin, an unsaturated polyester resin, or a polyurethane resin is preferable. A specific example of such an embodiment is a composite cable formed by impregnating a cable made of twisted carbon fibers carrying a thermosetting resin with the present dispersion, and then heating the cable to sinter the F polymer. Such a composite cable is useful as a cable for large structures, ground anchors, oil drilling, cranes, cableways, elevators, agriculture, forestry, fisheries, and slings. EXAMPLES

[0052] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these. The following materials were used: <pfa> PFA1: TFE units, NAH units and PPVE units are contained in the order of 97.9 mol%, 0.1 mol% and 2.0 mol%, respectively, and the carbonyl group is 1×10 6 Copolymer with 1000 molecules per unit (melting point: 300℃) PFA2: TFE units and PPVE units are contained in the order of 97.5 mol% and 2.5 mol%, respectively, and the carbonyl group is 1×10 6 Copolymer with 40 molecules per unit (melting point: 305℃)

[0053] <Surfactant> Surfactant 1: F(CF2)6CH2(OCH2CH2)7OCH2CH(CH3)OH <Water-soluble compounds> Water-soluble compound 1: Triethylene glycol monomethyl ether Water-soluble compound 2: Glycol monoalkyl ether (polyoxyethylene tridecyl ether) with an HLB value of 14, a static surface tension of 28 mN / m, and a boiling point of 100°C or higher. Water-soluble compound 3: Glycol monoalkyl ether (polyoxyethylene tridecyl ether) with an HLB value of 11, a static surface tension of 27 mN / m, and a boiling point of 100°C or higher.

[0054] [Example 1] Example of production of liquid composition 15 parts by mass of PFA1 particles (D50: 2.0 μm), 5 parts by mass of surfactant 1, and 80 parts by mass of water-soluble compound 1 were added to a pot, zirconia balls were added to the pot, and the pot was rolled at 150 rpm for 1 hour to obtain liquid composition 11. Next, the liquid composition 11 was subjected to a wet jet milling process using a wet jet milling device (manufactured by Joko Co., Ltd., "JN100"; flow path diameter: 100 μm). In the wet jet milling process, the temperature inside the flow path was set to 15° C., the pressurizing pressure was set to 150 MPa, and the number of flow path passes was set to 30, to obtain a liquid composition 12 containing PFA1 particles (D50: 0.3 μm).

[0055] [Example 2] Dispersion liquid production example 30 parts by mass of liquid composition 11 was added to 70 parts by mass of an aqueous dispersion containing 60% by mass of PTFE particles (D50: 0.3 μm) (manufactured by AGC, "AD-911E") to obtain dispersion 1 containing PTFE particles, PFA1 particles, water-soluble compound 1 and water (PFA1 / PTFE=1 / 9 (mass ratio)). Dispersion 2 was obtained in the same manner as Dispersion 1, except that Liquid Composition 12 was used instead of Liquid Composition 11.

[0056] Dispersion 3 was obtained in the same manner as Dispersion 1, except that ethylene glycol dimethyl ether was used instead of Water-soluble Compound 1. Dispersion 4 was obtained by mixing a polyoxyalkylene polymer having a molecular weight of 10,000 or more with an aqueous dispersion containing PTFE particles and PFA1 particles. Liquid composition 13 was obtained in the same manner as liquid composition 12, except that PFA2 particles (D50: 1.8 μm) were used instead of PFA1 particles (D50: 2.0 μm). Dispersion liquid 5 was obtained in the same manner as dispersion liquid 1, except that liquid composition 13 was used instead of liquid composition 11.

[0057] [Example 3] Evaluation example of dispersion liquid (part 1) Immediately after preparation of each dispersion, the dispersibility was visually confirmed and evaluated according to the following criteria. ○: No sediment was observed. △: Sediment was observed, but it dispersed when shaken by hand. ×: The mixture becomes mousse-like and cannot be dispersed by shaking with hands. The results are shown in Table 1.

[0058] [Table 1]

[0059] [Example 4] Evaluation example of dispersion liquid (part 2) Dispersion liquid 1 was applied to the surface of copper foil (thickness: 18 μm), dried at 100°C for 10 minutes, baked at 380°C for 10 minutes in a nitrogen gas atmosphere, and then slowly cooled to obtain laminate 1 in which copper foil and a polymer layer (thickness: 5 μm) containing PTFE and PFA1 were formed on the surface of the copper foil. Laminate 2 was obtained in the same manner as laminate 1, except that dispersion 2 was used instead of dispersion 1.

[0060] Rectangular samples (length: 100 mm, width: 10 mm) were cut out from the laminates 1 and 2. The sample was fixed at a position 50 mm from one end in the longitudinal direction, and the metal foil and the polymer layer were peeled off from one end in the longitudinal direction at an angle of 90° to the sample at a pulling speed of 50 mm / min. The maximum load applied at this time was measured as the peel strength (N / cm), and the peel strength of each laminate was 10 N / cm or more. The surfaces of the polymer layers of Laminates 1 and 2 were observed with an SEM (magnification: 30,000 times). As a result, a dense fibrous layer originating from PTFE was formed on both surfaces, and there were no defects.

[0061] [Example 5] Example of production of liquid composition and dispersion (part 2) 40 parts by mass of PFA1 particles (D50: 2.0 μm) and zirconia balls were added to a pot containing 5 parts by mass of water-soluble compound 2 and 55 parts by mass of water, and the pot was rolled at 150 rpm for 1 hour to obtain Liquid Composition 1A (viscosity: 37 mPa s). 40 parts by mass of PFA1 particles (D50: 2.0 μm) and zirconia balls were added to a pot containing 5 parts by mass of water-soluble compound 3 and 55 parts by mass of water, and the pot was rolled at 150 rpm for 1 hour to obtain Liquid Composition 1B (viscosity: 376 mPa s).

[0062] 40 parts by mass of PFA2 particles (D50: 1.8 μm) and zirconia balls were added to a pot containing 5 parts by mass of water-soluble compound 2 and 55 parts by mass of water, and the pot was rolled at 150 rpm for 1 hour to obtain Liquid Composition 1C (viscosity: 300 mPa s). The dispersibility of Liquid Composition 1A, Liquid Composition 1B, and Liquid Composition 1C was evaluated in the same manner as for the dispersions, and the results were given in that order as "good", "good", and "Δ". In particular, Liquid Composition 1A was a low-viscosity aqueous dispersion, and exhibited excellent mixability with an aqueous dispersion of PTFE (manufactured by AGC, "AD-911E"). [Industrial Applicability]

[0063] The dispersion of the present invention has excellent dispersion stability and can be used to manufacture molded products (films, impregnated products such as prepregs, laminates, etc.) that have the physical properties and substrate adhesion of PTFE. The dispersion of the present invention is useful as a material for antenna parts, printed circuit boards, aircraft parts, automobile parts, sports equipment, food industry products, paints, cosmetics, etc. In the case of printed circuit boards, it can also be used as a new printed circuit board material to replace conventional glass epoxy boards in order to prevent the temperature rise of printed circuit boards on which electronic components are densely mounted.

[0064] Specifically, they are useful as electric wire covering materials (aircraft electric wires, etc.), electrical insulating tape, insulating tape for oil drilling, materials for printed circuit boards, separation membranes (microfiltration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, etc.), electrode binders (for lithium secondary batteries, for fuel cells, etc.), copy rolls, covers for furniture, automobile dashboards, home appliances, etc., sliding parts (load bearings, sliding shafts, valves, bearings, bushes, seals, thrust washers, wear rings, pistons, slide switches, gears, cams, belt conveyors, food transport belts, etc.), wear pads, wear strips, tube lamps, test sockets, wafer guides, wear parts for centrifugal pumps, hydrocarbon / chemical and water supply pumps, tools (shovels, files, saws, etc.), boilers, hoppers, pipes, ovens, baking molds, chutes, dies, toilets, container covering materials, and coating materials for the inside and outside of glass containers. Examples of glass containers include vials, syringes, syringes with needles, cartridge-type syringes, and ampoules.

[0065] The dispersion of the present invention further comprising a conductive filler can also be used in applications requiring electrical conductivity, such as in the field of printed electronics, for example, in the manufacture of current-carrying elements in printed circuit boards, sensor electrodes, displays, backplanes, RFID (radio frequency identification), photovoltaics, lighting, disposable electronic devices, automotive heaters, electromagnetic interference (EMI) shields, membrane switches, etc.

[0066] In addition, the molded product obtained from the dispersion of the present invention can be used as an adhesive for bonding electronic components such as IC chips, resistors, and capacitors mounted on a substrate in semiconductor elements, high-density substrates, and module components, bonding a circuit substrate to a heat sink, and bonding an LED chip to a substrate. Furthermore, the molded product can also be used as a conductive bonding material (an alternative to solder bonding) between circuit wiring and electronic components in the mounting process of electronic components. It can also be used as an adhesive between ceramic parts and metal parts in an in-vehicle engine. The molded product can also be used for the applications described in paragraph number

[0149] of International Publication WO 2016 / 017801.< / pfa>

Claims

1. A method for producing an impregnated woven fabric, comprising impregnating a woven fabric with a dispersion containing particles of polytetrafluoroethylene, particles of a tetrafluoroethylene-based polymer containing units based on perfluoro(alkyl vinyl ether), at least one water-soluble compound selected from the group consisting of glycol, glycol monoether and glycol monoacetate and having a boiling point of 100°C or higher, and water, and heating the resulting fabric to obtain an impregnated woven fabric containing the polytetrafluoroethylene and the tetrafluoroethylene-based polymer.

2. A method for producing an impregnated woven fabric as described in claim 1, wherein the water-soluble compound is a glycol monoalkyl ether, a glycol monoaryl ether, a glycol monoalkyl ether acetate or a glycol monoaryl ether acetate.

3. A method for producing an impregnated woven fabric as described in claim 1 or 2, wherein the tetrafluoroethylene-based polymer is a tetrafluoroethylene-based polymer having an oxygen-containing polar group containing a unit based on perfluoro(alkyl vinyl ether), or a tetrafluoroethylene-based polymer not having an oxygen-containing polar group containing said unit and containing 2.0 to 5.0 mol % of said unit relative to the total units.

4. A method for producing an impregnated woven fabric described in any one of claims 1 to 3, wherein the average particle diameter of the polytetrafluoroethylene particles is 0.01 to 1 μm and the average particle diameter of the tetrafluoroethylene-based polymer particles is 0.01 to 10 μm.

5. A method for producing an impregnated woven fabric described in any one of claims 1 to 4, wherein the mass ratio of the content of the tetrafluoroethylene-based polymer to the content of the polytetrafluoroethylene is 0.4 or less.

6. A method for producing an impregnated woven fabric described in any one of claims 1 to 5, wherein the mass ratio of the content of the water-soluble compound to the content of the water is 2 or less.

Citation Information

Patent Citations

  • For a polymer processing aid

    JP1991505347A

  • Coating product

    JP1996300560A

  • Dispersion composition of fluorine containing meltable resin and coated product

    JP2001164064A

  • Aqueous dispersion of fluoropolymer capable of melt processing

    JP2001207005A

  • Fluorine-containing material dispersion aqueous composition, method for producing coated article and coated article

    JP2003171519A